Problem Based Learning Model Assisted by Puzzle Media to Improve Learning Outcomes of Elementary School Students 102078 Block Zero Jangga in Islamic Education Learning - Awwaliyah, Wannasiah; Siregar, Tanti Widyaningsih (Journal of Indonesian Primary School, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning by using a problem-based learning model with the help of puzzle media. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. Data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the problem-based learning model with the help of puzzle media can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of pre-cycle 48.71%, cycle I 66.39% and in cycle II increasing to 89.66%. Thus, the use of a problem-based learning model with the help of puzzle media can be used as an alternative to improve student learning outcomes in Islamic religious education learning.